The role of multi-functionality in social preferences toward semi-arid rural landscapes: An ecosystem service approach - García-Llorente, Marina; Martín-López, Berta; Iniesta-Arandia, Irene; López-Santiago, César a; Aguilera, Pedro a; Montes, Carlos (Environmental Science & Policy, 2012)
The present study analyzes the relationship between landscape multi-functionality and social preferences toward Mediterranean landscapes in terms of monetary and nonmonetary techniques. Twenty landscape views were selected as representative of the landscape units characterizing Nacimiento and Adra semi-arid watersheds (southeastern Spain). Face-to-face questionnaires were used to assess social factors that inﬂuence willingness to pay for aesthetic landscape enjoyment (use value) and landscape conservation (non-use value). Meanwhile, an expert focus group analyzed the capacity of the selected semi-arid ecosystems for supplying services to society. The favorite landscape views mainly contained steeper reliefs, water ﬂows, and traditional human activities. Our results suggest a strong positive effect between respondents’ place attachment and the level of support for landscape conservation. Respondents were more willing to pay for the conservation of semiarid rural landscapes when their sense of belonging was greater. We also found that multifunctional landscapes, which provide higher numbers of regulating and cultural services, were also preferred in terms of their visual quality (use value). Additionally, they had more social support for their conservation (non-use value). The conversion of multi-functional landscapes to mono-functional ones disturbs the stability of rural areas, their capacity to provide other ecosystem services, and the social support toward their preservation. To reverse this tendency, two major ideas should be emphasized. The ﬁrst is the necessity of considering the ecological components and processes behind landscapes, and the second is the role of the local population on rural landscape conservation
Keywords: Contingent valuation; Expert focus group; Landscape aesthetic; Mediterranean; Social–ecological system; Value

Preferencias de los propietarios e intervención pública: el caso de las dehesas de la comarca de Monfragüe - CAMPOS PALACIN, P; Mariscal Lorente, P J (Investigación Agraria: Sistemas y Recursos Forestales, 2003)
The public have an increasing interest in Dehesa environmental services (recreation, option and existence values). The growing Government incentives on environmental friendly agricultural practices have given a new opportunity for private economics of natural and environmental resources in Dehesa. This work presents the results from a Delphi questionnaire on owners’ preferences and demands of compensations for undertaking environmental conservation and improvement measures in Dehesa of Monfragüe shire. The private owners of Dehesa are investors that have, at the same time, commercial aims and private environmental services autoconsumption preferences. A contingent valuation questionnaire has been applied to a group of Dehesa ’ owners to measure the maximum willingness to pay (WTP) —to accept losses— of commercial capital income against the maintenance of private environmental services autoconsumption. The Delphi results show that owners’attitude is in favour to follow the environmental friendly agricultural practices, when the Government incentives are higher than the losses of commercial capital income plus a risk premium. The value of owners’ autoconsumption measured by the WTP question from the contingent valuation gives an autoconsumption profitability rate from 1% to 5% of the total market value of the Dehesa.
Keywords: Contingent valuation; Dehesa; Delphi technique; environmental and agroforestry practices; environmental autoconsumption services; Hicksian income

Preferencias de los propietarios e intervención pública: el caso de las dehesas de la comarca de Monfragüe - Campos Palacín, P.; Mariscal Lorente, P. J. (Investigación Agraria: Sistemas y Recursos Forestales, 2003)
The public have an increasing interest in Dehesa environmental services (recreation, option and existence values). The growing Government incentives on environmental friendly agricultural practices have given a new opportunity for private economics of natural and environmental resources in Dehesa. This work presents the results from a Delphi questionnaire on owners’ preferences and demands of compensations for undertaking environmental conservation and improvement measures in Dehesa of Monfragüe shire. The private owners of Dehesa are investors that have, at the same time, commercial aims and private environmental services autoconsumption preferences. A contingent valuation questionnaire has been applied to a group of Dehesa ’ owners to measure the maximum willingness to pay (WTP) —to accept losses— of commercial capital income against the maintenance of private environmental services autoconsumption. The Delphi results show that owners’attitude is in favour to follow the environmental friendly agricultural practices, when the Government incentives are higher than the losses of commercial capital income plus a risk premium. The value of owners’ autoconsumption measured by the WTP question from the contingent valuation gives an autoconsumption profitability rate from 1% to 5% of the total market value of the Dehesa.
Keywords: Contingent valuation; Dehesa; Delphi technique; environmental and agroforestry practices; environmental autoconsumption services; Hicksian income